Comparative Studies of Packed Cell Volume, Haemoglobin, Total Protein, Haemagglutination Inhibition Antibodies and Rectal Temperature of Pigeons (Columbia livia) Administered Newcastle Disease Virus Through Different Routes - Oladele, S.B.; Morou, M.; Sambo, S.J.; Ibu, O.J. (International Journal of Poultry Science, 2008)
Comparative studies of packed cell volume (PCV), haemoglobin (HB), total protein (TP), haemagglutination inhibition (HI) antibodies and rectal temperature (RT) were carried out on a total of 50 pigeons (Columbia livia) that were administered Newcastle disease virus (NDV) Kudu 113 strain through different routes. Fifteen pigeons were administered 0.2 mL each of NDV Kudu 113 strain per os (po), 15 pigeons were inoculated with 0.2 mL of the virus intramuscularly (im), another 15 pigeons were sprayed with about 0.2 mL each of the virus through oculonasal (oc) route, while 15 pigeons served as control. Clinical signs and lesions of Newcastle disease (ND) were observed in some of the infected pigeons. After infection, there was an increase in HI antibodies, reaching the maximum mean values of log2 5.2 ± 0.13, log2 5.3 ± 0.31 and log2 5.0 ± 0.12 in pigeons that were administered NDV Kudu 113 strain through oc, po and im routes, respectively. Similarly, as soon as patent infection was established, the RT continued to rise and attained peak values of 42.31 ± 0.03, 41.94 ± 0.06 and 42.18 ± 0.06 °C in pigeons that were administered the virus through po, im and oc routes, respectively. The values of PCV, HB, TP, HI and RT for the control pigeons were relatively constant, while the corresponding values in the infected pigeons fluctuated widely, depending on the route of administration of the virus. It was concluded that vital blood and body parameters, such as PCV, HB, TP, HI and RT were altered during infection of pigeons with NDV Kudu 113 strain.